The role of pilot judgments of the European Court of Human Rights in addressing the issue of the right to a trial within a reasonable time - Strnad, Nataša (Pravnik, 2015)
The European Court of Human Rights (ECHR) is faced with a rising number of cases concerning the right to a trial within a reasonable time. This shows that the majority of member states of Council of Europe is faced with a systemic problem concerning the length of court proceedings. In an attempt to deal with this situation, the ECHR, when it started noting similar cases, identified systemic problems and then, when solving a particular case, invoked Article 46 of the European Convention on Human Rights, which obligates the states to abide by the judgments, to which they are parties, as ground for imposing general binding obligations to the state (quasi-pilot judgments). On 21 February 2011 it adopted a new rule (Rule 61) concerning the Pilot-judgment procedure. The pilot judgment procedure is applicable in cases where there exists in a Contracting Party a structural or systemic problem that could arise several related claims. In this article the authors examine whether the (quasi) pilot judgment procedure is always an appropriate way to deal with situations where there has been a violation of the right to trial within a reasonable time. Suggestions are made on other possible ways to confront the problem both on part of ECHR and on part of the Contracting Parties. Possibilities include increasing alternative dispute resolution as well as curbing (abandoning) the state monopoly in conducting judicial proceedings.
Keywords: človekove pravice; European Union; Evropska unija; Evropsko sodišče za človekove pravice; human rights; roki; Slovenia; Slovenija; sodišča; sodne odločbe; sodni postopek